Maternal Supplementation With Different Probiotic Mixture From Late Pregnancy to Day 21 Postpartum: Consequences for Litter Size, Plasma and Colostrum Parameters, and Fecal Microbiota and Metabolites in Sows - Han, Li; Azad, Md. Abul Kalam; Huang, Pan; Wang, Wei; Zhang, Wenming; Blachier, Francois; Kong, Xiangfeng (Frontiers in Veterinary Science, 2022)
The present study determined the effects of different probiotic mixture supplementation to sows from late pregnancy to day 21 postpartum on reproductive performance, colostrum composition, plasma biochemical parameters, and fecal microbiota and metabolites. A total of 80 pregnant sows were randomly assigned to one of four groups (20 sows per group). The sows in the control group (CON group) were fed a basal diet, and those in the BS-A+B, BS-A+BL, and BS-B+BL groups were fed basal diets supplemented with 250 g/t of different probiotic mixture containing either 125 g/t of Bacillus subtilis A (BS-A), Bacillus subtilis B (BS-B), and/or Bacillus licheniformis (BL), respectively. The trial period was from day 85 of pregnancy to day 21 postpartum. The results showed that different dietary probiotic mixture supplementation increased (P < 0.05) the average weaning weight and average daily gain of piglets, while dietary BS-A+BL supplementation increased the number of weaned piglets (P < 0.05), litter weight (P = 0.06), litter weight gain (P = 0.06), and litter daily gain (P = 0.06) at weaning compared with the CON group. Different dietary probiotic mixture supplementation improved (P < 0.05) the colostrum quality by increasing the fat and dry matter concentrations, as well as the protein and urea nitrogen concentrations in the BS-A+BL group. Dietary probiotic mixture BS-B+BL increased the plasma total protein on days 1 and 21 postpartum while decreased the plasma albumin on day 1 postpartum (P < 0.05). In addition, the plasma high-density lipoprotein-cholesterol was increased in the BS-A+B and BS-B+BL groups on day 21 postpartum, while plasma ammonia was decreased in the BS-A+B and BS-A+BL groups on day 1 and in the three probiotic mixtures groups on day 21 postpartum (P < 0.05). Dietary supplementation with different probiotic mixture also modified the fecal microbiota composition and metabolic activity in sows during pregnancy and postpartum stages. Collectively, these findings suggest that maternal supplementation with Bacillus subtilis in combination with Bacillus licheniformis are promising strategies for improving the reproductive performance and the overall health indicators in sows, as well as the growth of their offspring.